Emission and collisional correlation in far-off equilibrium quantum systems - Heraud, J.; Vincendon, M.; Reinhard, Paul-Gerhard; Dinh, P. M.; Suraud, E. (European Physical Journal D, 2021)
Abstract: We propose a scheme to describe dynamical correlations in finite fermion systems which are open in the sense that they can lose particles, electrons in the present case. It is built as an extension of recently developed schemes to describe dissipative dynamics in finite fermion systems, namely stochastic time-dependent adiabatic local-density approximation (STDLDA) and its averaged version, ASTDLDA, so far being applied only in closed systems. STDLDA and ASTDLDA are based on real-time real-space dynamics in terms of time-dependent density functional theory and add dynamical two-body collisions in a stochastic manner. The extension to systems that can emit electrons is achieved by complementing the complete (numerical) description of wave functions in “inner” space (inside the computation box) through a global description in “outer” space (outside the computation box) and a careful bookkeeping of flow between inner and outer regions. We test the method in a 1D model system, mimicking simple molecules or clusters. Two test cases are investigated: a metal-like system excited by an instantaneous dipole boost, and a covalent-like system excited by an instantaneous one-particle–one-hole transition. The dynamics is analyzed in terms of one-body observables (dipole moment, ionization, entropy). STDLDA and ASTDLDA exhibit clearly dissipative features at variance with mean-field dynamics. Unlike the pattern in closed systems, differences between STDLDA and ASTDLDA show up for ionization. They can be attributed to significantly larger fluctuations of the mean field in STDLDA. Graphic Abstract: [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2021-04-23